2008
DOI: 10.2174/156720508784533286
|View full text |Cite
|
Sign up to set email alerts
|

Functional Consequences of Locus Coeruleus Degeneration in Alzheimers Disease

Abstract: Alzheimer's disease (AD) is the most common cause of cognitive impairment in older patients, and its prevalence is expected to soar in coming decades. Neuropathologically, AD is characterized by beta-amyloid-containing plaques, tau-containing neurofibrillary tangles, and cholinergic neuronal loss. In addition to the hallmark of memory loss, the disease is associated with other neuropsychiatric and behavioral abnormalities, including psychosis, aggression, and depression. Although cholinergic cell loss is clear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
142
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(146 citation statements)
references
References 43 publications
3
142
0
1
Order By: Relevance
“…7 Some reports suggest that a reduction in the number of noradrenergic neurons affects the accumulation of ␤-amyloid, inflammation, or microcirculation in the LC. 23,24 Our NmMRI study could not identify a significant signal reduction in the LC of patients with Alzheimer disease. Busch et al 25 reported that the LC begins to lose cells only during the later stages of Alzheimer disease.…”
Section: Discussionmentioning
confidence: 60%
“…7 Some reports suggest that a reduction in the number of noradrenergic neurons affects the accumulation of ␤-amyloid, inflammation, or microcirculation in the LC. 23,24 Our NmMRI study could not identify a significant signal reduction in the LC of patients with Alzheimer disease. Busch et al 25 reported that the LC begins to lose cells only during the later stages of Alzheimer disease.…”
Section: Discussionmentioning
confidence: 60%
“…Interestingly, LC cell death is either very limited or nonexistent in transgenic mice models of Alzheimer's disease [115]. Thus, in the next part of our study we applied knockout mice for different SST receptors (SSTR1, 2, 4) and their wild-type littermates, to further study a potential role of SSTR2 signalling in the maintenance of the noradrenergic system.…”
Section: Peripheral Noradrenergic Nerves Do Not Show Signs Of Degenermentioning
confidence: 99%
“…The currently used mouse models of Alzheimer's disease (transgenic mice expressing mutant forms of amyloid precursor protein (APP), presenilins and tau, singly or in combination), however, exhibit at most mild LC degeneration or no degeneration at all [115,45]. In contrast, a selective.…”
Section: Introductionmentioning
confidence: 99%
“…In AD patients the central portion of the LC, which is considered to project predominantly to the hippocampus, frontal and temporal cortex areas that are usually severely affected by senile plaque and neurofibrillary tangle formation, shows the most extensive loss of cells (Marcyniuk et al, 1986). The decreased LC neuron numbers are significantly correlated with the increase of amyloid plaques, neurofibrillary tangles, and severity of dementia (Marcyniuk et al, 1986;Bondareff et al, 1987;Grudzien et al, 2007;Weinshenker, 2008). In rodent AD models, neurotoxin N-(2-chloroethyl)-N-ethyl-bromobenzylamine (DSP4)-induced LC neuron degeneration and NE deficiency exacerbate A␤ deposition, inflammation, neurodegeneration in brain, and cognitive impairment (Heneka et al, 2006;Kalinin et al, 2007).…”
Section: Introductionmentioning
confidence: 99%